How to deal with knowledge in small companies? Defining emergent KM approach - Ettore Bolisani; Enrico Scarso; Malgorzata Zieba (Gdańsk University of Technology, Faculty of Management and Economics, 2015)
This paper examines the concept of emergent KM approach in small companies. The origins of consideration are grounded in the theory of strategic management literature and in particular in the distinction between deliberate versus emergent approach towards strategic planning. Using the methodology of case study, we carried out an explorative research to analyse the characteristics of KM approach in two small companies located in Italy and Poland. Both companies appeared to follow emergent KM approach and therefore, a detailed analysis of this phenomenon was feasible. A description of the main features of an emergent KM approach is then proposed. On the basis of research results, implications for both managers and researchers are discussed.
Keywords: L84; M1; 330; knowledge management; KM; SMEs; ICT services providers; Italy; Poland